1998
DOI: 10.1597/1545-1569_1998_035_0120_aceocm_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

A Cephalometric Evaluation of Craniofacial Morphology in Familial Dysautonomia

Abstract: Objective The purpose of this study was to delineate the craniofacial and dentoalveolar morphology of patients with familial dysautonomia (FD) in order to contribute to the understanding of the association between progressive sensory and autonomic neuropathy and the characteristic appearance of the dys-autonomic face. Patients The study group comprised 32 patients with FD (15 females and 17 males; mean age 10.8 years, SD 3.5 years, range 5.8-19.8 years). Design Lateral cephalograms from each patient were trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These findings, in addition to the lack of coordination of the oral and peri‐oral muscle activity, have indicated that most patients with FD have moderate to severe malocclusions of the kind that hinder normal mastication, swallowing, and speech 21 . A cephalometric evaluation of craniofacial morphology of children with FD further confirmed these observations 25 …”
Section: General Oral and Dental Statusmentioning
confidence: 74%
See 4 more Smart Citations
“…These findings, in addition to the lack of coordination of the oral and peri‐oral muscle activity, have indicated that most patients with FD have moderate to severe malocclusions of the kind that hinder normal mastication, swallowing, and speech 21 . A cephalometric evaluation of craniofacial morphology of children with FD further confirmed these observations 25 …”
Section: General Oral and Dental Statusmentioning
confidence: 74%
“…In addition to short stature and skeletal deformities, the craniofacial morphology of patients with FD is significantly different, in some parameters, from the “classical” accepted norms, but resembles those of patients of the same ethnic origin (Jews of Eastern European origin) 25 . However, despite the overall resemblance, the mandible is retro‐gnathic and has a steep plane angle and its growth axis is more horizontal.…”
Section: Craniofacial Morphologymentioning
confidence: 93%
See 3 more Smart Citations